Phytohormones as Growth Regulators During Abiotic Stress Tolerance in Plants - EL Sabagh, Ayman; Islam, Mohammad Sohidul; Hossain, Akbar; Iqbal, Muhammad Aamir; Mubeen, Muhammad; Waleed, Mirza; Reginato, Mariana; Battaglia, Martin; Ahmed, Sharif; Rehman, Abdul; Arif, Muhammad; Athar, Habib-Ur-Rehman; et al. (Frontiers in Agronomy, 2022)
Phytohormones (PHs) play crucial role in regulation of various physiological and biochemical processes that govern plant growth and yield under optimal and stress conditions. The interaction of these PHs is crucial for plant survival under stressful environments as they trigger signaling pathways. Hormonal cross regulation initiate a cascade of reactions which finely tune the physiological processes in plant architecture that help plant to grow under suboptimal growth conditions. Recently, various studies have highlighted the role of PHs such as abscisic acid, salicylic acid, ethylene, and jasmonates in the plant responses toward environmental stresses. The involvement of cytokinins, gibberellins, auxin, and relatively novel PHs such as strigolactones and brassinosteroids in plant growth and development has been documented under normal and stress conditions. The recent identification of the first plant melatonin receptor opened the door to this regulatory molecule being considered a new plant hormone. However, polyamines, which are not considered PHs, have been included in this chapter. Various microbes produce and secrete hormones which helped the plants in nutrient uptake such as N, P, and Fe. Exogenous use of such microbes help plants in correcting nutrient deficiency under abiotic stresses. This chapter focused on the recent developments in the knowledge related to PHs and their involvement in abiotic stresses of anticipation, signaling, cross-talk, and activation of response mechanisms. In view of role of hormones and capability of microbes in producing hormones, we propose the use of hormones and microbes as potential strategy for crop stress management.